2004
DOI: 10.1145/974121.974131
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art in privacy preserving data mining

Abstract: We provide here an overview of the new and rapidly emerging research area of privacy preserving data mining. We also propose a classi cation hierarchy that sets the basis for analyzing the work which has been performed in this context. A detailed review of the work accomplished in this area is also given, along with the coordinates of each work to the classi cation hierarchy. A brief evaluation is performed, and some initial conclusions are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
334
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 653 publications
(341 citation statements)
references
References 23 publications
0
334
0
7
Order By: Relevance
“…Privacy-preserving record linkage with exact matching is very similar to privacy-preserving set intersection: to identify the intersection of two sets of records without revealing private records. Surveys could be found at [26,11]. Among the more popular approaches, solutions based on homomorphic encryption (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Privacy-preserving record linkage with exact matching is very similar to privacy-preserving set intersection: to identify the intersection of two sets of records without revealing private records. Surveys could be found at [26,11]. Among the more popular approaches, solutions based on homomorphic encryption (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Kantarcioglu and Clifton [7] suggested that adopting a common framework for discussing privacy preservation will enable next generation data mining technology to make substantial advances in alleviating privacy concerns. Verykios et al [28] analyzed the state-ofthe-art, classified the proposed algorithms from five different dimensions: data distribution, data modification, data mining algorithm, data or rule hiding, and privacy preservation. They also suggested a set of metrics for assessing PPDM performance.…”
Section: Related Workmentioning
confidence: 99%
“…PPDM is concerned with extraction of information from data warehouse without revealing sensitive information of individuals and company privacy details [8], [9], [10]. Present industry consists of database which is distributed across multiple source locations.…”
Section: Introductionmentioning
confidence: 99%